Needs Analysis on the Development of Instructional Material for Intensive Listening Course - Agus Gozali (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
Need analysis is pivotal before developing materials or syllabus. Some studies indicated the importance of conducting a needs analysis. Although many researchers had already conducted needs analysis studies, there is a lack of proper material that can accommodate the students to learn intensive listening courses, especially during the covid-19 pandemic. This study aimed to get the information that will be beneficial to compose the material of the Intensive Listening course. One hundred and twenty sophomores were employed in a survey study to describe what their needs are related to their listening skills. A close-ended questionnaire was employed to find the students’ needs. The findings indicated that 3 important things can affect the material development process such as materials that students need, the method that the teacher used, and students’ range of proficiency. The result implied that in the process of teaching listening and developing listening materials, the lecturer should be aware of the topics, media, and students' proficiency.